Q: What is 6x - 4y 7y - 2x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

10x - 3y + 2x - 4y =(10x + 2x) + (-3y - 4y) =12x - 7y

2x + 4y - 5x + 3y = 7y - 3x

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

It is the same as: 6x+4y

6x - 4y

Related questions

6x plus 4y

Combine like terms: -2x - 4y + 5x - 7y = 3x - 11y -2x + 5x = 3x -4y + -7y = -11y

10x - 3y + 2x - 4y =(10x + 2x) + (-3y - 4y) =12x - 7y

2x + 4y - 5x + 3y = 7y - 3x

10x+2x-3y-4y=12x-7y

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

the solution to the system of equations 6x + 7y = 20 and y = 2x is (x, y) = (1, 2)

It is the same as: 6x+4y

6x - 4y

41

3x + 7y

4x + 3y - 2x - 7y2x - 4y